Globalisation and national incentives for protecting environmental goods - Alkuin Kölliker (Max Planck Institute for Research on Collective Goods, 2004)
This article tries to explain national incentives for protecting environmental goods either autonomously or collectively; it explores how globalisation has affected those incentives; and it suggests how national environmental policy might respond so as to ensure its effectiveness. The central argument is that national incentives for environmental protection may to a considerable extent be explained by a combination of the type of environmental good to be protected (in terms of public goods theory) and the effects of environmental protection measures on international competitiveness. Arrangements for protecting environmental goods can be ranked according to their centripetal effects on non-participating countries. Centripetal effects are strongest in the case of club goods (1), followed by private goods (2), public goods (3), and common pool resources (4). The centripetal effects resulting from the type of environmental good can be further reinforced by competitive advantages resulting from environmental protection measures; they can be weakened by competitive disadvantages; or they can remain unchanged due to competitive neutrality. The combination of four types of environmental goods and three types of competitive effects (positive, negative, neutral) results in twelve possible cases, with differing national incentives for autonomous and collective environmental protection. Given specific assumptions, these twelve cases can be ranked with regard to the severity of collective action problems they involve. The article includes a short empirical illustration for each case. It also analyses how globalisation (in the form of increasing trade) and some of its driving forces (in the form of free trade agreements) influence national incentives and legal possibilities for environmental protection. This article concludes with a brief discussion of four options for (re-)expanding the action space for national environmental policies under the condition of economic globalisation.
Keywords: 330; Umweltschutz; Umweltpolitik; Öffentliche Güter; Internationale Umweltpolitik; Internationaler Wettbewerb; Komparativer Vorteil; Globalisierung